Kun-mkhyen-chen-po Dri-med-ʼod-zer gyis mdzad paʼi Phud rabs rgyas pa ʼdod stsol re skoṅ bklag chog tu bkod pa bźugs so - Kloṅ-chen-pa Dri-med-ʼod-zer, 1308-1363 (s.n., 1972)
Propitiatory rituals for the host of Lamaist protective deities.